The Effect of Group Counseling Intervention Focusing on Fear of Negative Social Evaluation, Social Support, and Substance Use Norms Among Sexual Minority Adults in Bangkok - Limthongsittikun, Thawatwong; Mohanan, Santhosh (Journal of The Royal Thai Army Nurses, 2025)
This study examined the effects of group counseling intervention targeting fear of negative social evaluation, social support, and substance use norms among sexual minority adults in Bangkok. Sixteen participants, recruited via snowball sampling, were randomly assigned to an experimental group or control group (eight per group). The experimental group attended eight weekly 60-minute sessions, while the control group completed a one-day word memorization task. Using validated Thai-language instruments including BFNE-S, Substance Use Injunctive Norms Scale, Thai-MSPSS, pre- and post-intervention assessments were analyzed with Repeated Measures ANOVA. Results showed significant reductions in fear of negative evaluation and increases in friend and significant-other support, with no changes in family support. Substance use norms significantly decreased for total and occasional use but not regular use. Findings suggest group counseling is effective in improving mental health outcomes for sexual minorities. Recommendations include culturally sensitive interventions for counselors, nurses, and policymakers, with future research exploring individualized approaches and sexual minority identities.